Cognitive coping strategies of South African women in breast cancer care. (December 2021) - Gallagher-Squires, Charlotte; Roomaney, Rizwana; Kagee, Ashraf
In this qualitative study, we explored the cognitive strategies used by South African women with breast cancer to cope with their cancer experience. The themes that emerged were reappraisal, acceptance, relinquishing control, and benefit finding. Reappraisal involved downward comparison, normalising experiences, and positive self-talk. Acceptance included accepting unpleasantness, preparing for future challenges, acceptance for healing, and spirituality. Relinquishing control included giving up, trust in God, and trust in doctors. Benefit finding included spiritual growth, personal growth, altruism, and appreciation of life. To our knowledge, these were the first data to document South African women's experiences of coping with breast cancer.